Family Involvement And Innovation in Family Business in Indonesia: The Moderating Role of Family Member Composition - Muhammad Arief; Abel Tasman (CV. Muris Global Education, 2026)
In Indonesia, family businesses contribute approximately 25% to Gross Domestic Product (GDP) and operate across various economic sectors, from small and medium enterprises to public companies listed on the Indonesia Stock Exchange. Family firms play a significant role in the Indonesian economy, yet their innovation activities often face challenges related to family control and risk aversion. This study examines the effect of family involvement on firm innovation and the moderating role of family composition. Using panel data from 25 family firms listed on the Indonesia Stock Exchange during 2020–2024, this study analyzes 125 firm-year observations. Family involvement is measured by family ownership, while innovation is represented by R&D intensity. Family composition is classified into controlling owner structures, sibling partnerships, and cousin consortia. Panel data regression and Moderated Regression Analysis (MRA) are used. The results indicate that family involvement negatively and significantly affects firm innovation. However, family composition does not significantly moderate this relationship. These findings support the Socioemotional Wealth perspective, which suggests that family owners tend to prioritize preserving control and socioemotional wealth over investing in innovation.